The autophagic biomarker p62 as a tool for monitoring age-dependent cellular responses - Carvalho, Ana Virgínia Alves (2021)
The process of protein synthesis is error prone, thus, there is a cellular quality control system which is prepared to detect these errors and to degrade these damaged proteins. Upon failure from the cellular quality control system, there can be an accumulation of protein aggregates, which is associated with neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease, which are aging-associated disorders. Aging cells are known to have a reduced ability to eliminate misfolded and aggregated proteins; furthermore, aged cells experience extended cumulative oxidative stress, leading to an increase in transcriptional and translational errors. Much of intracellular protein degradation is performed by the proteasome, which plays an important role in the regulation of the cell cycle. Another process, autophagy, is an intracellular lysosomal degradation process, which is induced by starvation or extracellular stressors, and consists in the formation of an autophagosome that sequesters cytoplasm and the cellular content to be degraded. p62/SQSTM1 protein is an autophagy receptor, which is translocated to autophagy substrates and binds to them, facilitating their sequestration and degradation by autophagy. The objective of this thesis was to understand how extracellular stressors (proteasome inhibition, starvation, mitochondrial membrane depolarization, antioxidant agents) modulate the autophagy response on fibroblasts of different age groups (21, 41, 69, and 80 years old), as well as to understand the influence of aging on the autophagic response to stressors. A western blot analysis showed that starvation caused accumulation of p62 in 41-yearolds. Upon mitochondrial membrane depolarization, there was a general increase in autophagy, except on young cells; combined membrane depolarization and proteasome inhibition caused a decline in p62 in all age groups. Catechin-induced antioxidation caused an increase in autophagy, as p62 concentration reduced in all age groups. Proteasome inhibition together with antioxidation caused a significant increase in autophagy on 41-yearolds. It would be relevant to continue to pursue this area, possibly complementing these results with further studies and more techniques. Hence, the underlying hypothesis of this study was proved true, as p62 is a good biomarker for autophagy monitoring on cells of different ages, upon extracellular stress